Corrigendum to: A Galois Correspondence for Reduced Crossed Products of Simple $\text{C}^{* }$-algebras by Discrete Groups. (30th April 2020) - Cameron, Jan; Smith, Roger R.
Abstract: This note corrects an error in our paper "A Galois correspondence for reduced crossed products of unital simple $\text{C}^{* }$ -algebras by discrete groups", http://dx.doi.org/10.4153/CJM-2018-014-6 . The main results of the original paper are unchanged.